Antibacterial activity of hexane and methanol fractions of some selected plants against Klebsiella pneumoniae - Yosie Andriani; Wahdini Hanifah; Alifa Husnun Kholieqoh; Fadzilah Adibah Abdul Majid; Hermansyah Hermansyah; Hermansyah Amir; Tengku Sifzizul Tengku Muhammad (Wolters Kluwer Medknow Publications, 2023)
Besides adenovirus, pneumonia can also be caused by bacteria. One of the most common bacteria causing the pneumonia is Klebsiella pneumoniae. Currently, treatment by antibiotics has been widely used. Nevertheless, the increasing failure of existing antibiotics because of antibiotic resistance resulted by bacterial pathogens has become a serious problem to human health. Hence, there is a need for a new antibacterial potential agent against K. pneumoniae as an alternative treatment to the pneumonia to prevent the risk of a severe pneumonia for both healthy people and those already infected with the pneumonia. This study, therefore, investigated the antibacterial activity of some selected plants (Pandanus tectorius, Nypa fruticans, Sonneratia alba, Phaleria macrocarpa, Hibiscus tiliaceus, and Pongamia pinnata) against K. pneumoniae. In this study, samples were extracted successively by cold maceration using hexane and methanol. Antibacterial activity was determined by well and disc diffusion methods. Each fraction was prepared by two-fold dilutions from 20 mg/mL to 0.156 mg/mL. All data were analyzed in triplicate replication and presented as mean values ± standard deviation. Results showed that all methanol fractions of selected plants had antibacterial activity against K. pneumoniae, and well-diffusion method showed better antibacterial results compared to the agar well-diffusion method. The strongest activity was obtained by methanol fraction of S. alba leaf, followed by P. pinnata leaf, Nypa fruticans bark, H. tiliaceus leaf, P. macrocarpa leaf, and P. tectorius leaf with the minimum inhibitory concentrations (MICs) value between 0.625 and 5.0 mg/mL. Phytochemical screening revealed that all methanol fractions were rich in flavonoid content, which could have contributed to their antibacterial activity.